Pelatihan Penggunaan Hoax Buster Tools pada Anggota Karang Taruna dan PKK di Sukoharjo - Fathan Fathan; Rhesa Zuhriya Pratiwi (UIN Raden Mas Said Surakarta, 2020)
The purpose of the service activities carried out by the KPI FUD IAIN Surakarta Study Program is to provide training in using the Hoax Buster Tools for the community, especially youth members of the Youth Organization and PKK mothers in Sukoharjo. The target segmentation is youth of the PERSI Youth Organization in Banmati Village, Sukoharjo District, as well as women members of the PKK Movement in Pucangan Village, Kartasura District, Sukoharjo. Community service activities run smoothly. Both youths and mothers who participated in the activity seemed enthusiastic and active in participating. Through this training, the participants were introduced to the forms and types of hoaxes, how to recognize and identify hoaxes, and verify hoaxes circulating in the community. It is hoped that this service activity can continue, in order to provide education to the public about the importance of media literacy in the digital realm.